Enhancing The pH Value of Black Soil Using Electrokinetic Remediation Technique - Faizul, Muhammad Alif Najwan; Hishamuddin, Amir Syahmi; Ahmad, Nur Afifah Alezah; Mohammad Azmi, Mohamad Azim (Multidisciplinary Applied Research and Innovation, 2024)
Electrokinetic Remediation (EKR) is a low-cost, effective, and environmentally benign process for removing multiple heavy metals from damaged soil at the same time. It entails placing electrodes into the soil around the contaminated area and delivering a low voltage to the electrode, causing pollutants to migrate to the electrode by electromigration, electroosmosis, and electrophoresis. Soil pH is a key aspect that can influence the effect of EK remediation on contaminated soil restoration. Using varied voltages for 6 weeks, this study determined the change in pH value in acidic to neutral soil. Before EKR, the pH of black soil was 4.5, and it increased in a variety of patterns depending on the treatment duration. The greater the curing day of the treatment, the higher the pH value of the black soil. The suggested duration and voltage for EK remediation are 14 days and 20V, respectively. One of the criteria that can affect soil pH while utilising EK therapy is the strength of the applied voltage.